Perinatally infected adolescents living with human immunodeficiency virus (perinatally human immunodeficiency virus) - Cruz, Maria Leticia S (World J Virol, 2015)
The availability of highly potent antiretroviral treatment during the last decades has transformed human immunodeficiency virus (HIV) infection into a chronic disease. Children that were diagnosed during the first months or years of life and received treatment, are living longer and better and are presently reaching adolescence and adulthood. Perinatally HIV-infected adolescents (PHIV) and young adults may present specific clinical, behavior and social characteristics and demands. We have performed a literature review about different aspects that have to be considered in the care and follow-up of PHIV. The search included papers in the MEDLINE database via PubMed, located using the keywords “perinatally HIV-infected” AND “adolescents”. Only articles published in English or Portuguese from 2003 to 2014 were selected. The types of articles included original research, systematic reviews, and quantitative or qualitative studies; case reports and case series were excluded. Results are presented in the following topics: “Puberal development and sexual maturation”, “Growth in weight and height”, “Bone metabolism during adolescence”, “Metabolic complications”, “Brain development, cognition and mental health”, “Reproductive health”, “Viral drug resistance” and “Transition to adult outpatient care”. We hope that this review will support the work of pediatricians, clinicians and infectious diseases specialists that are receiving these subjects to continue treatment.